SYNTHESIS, STRUCTURAL STUDY, AND MAGNETIC SUSCEPTIBILITY OF THE CHALCOGENIDE OLIVINE COMPOUND Mn2SiTe4 - Gerzon E Delgado; Pilar Delgado-Niño; Cecilia Chacón; Gustavo Marroquin; Iván Brito (Journal of the Chilean Chemical Society, 2024)
The ternary material Mn2SiTe4 was synthesized by direct fusion using the annealing method. X-ray powder diffraction analysis indicated that this material crystallizes in the olivine-type structure, space group Pnma, Z = 4, with unit cell parameters: a = 13.905(2) Å, b = 8.128(1) Å, c = 6.526(1) Å, V = 737.6(2) Å3. This olivine structure can be described from a hexagonal close-packing of selenium atoms where manganese atoms occupy ½ of the octahedral sites while silicon atoms lay in ⅛ of the tetrahedra. The magnetic susceptibility curve indicate a possible antiferromagnetic behavior for this material. This compound is related to the ternary layered Mn3Si2Te6 recently studied as possible two-dimensional (2D) magnetic material.